2018
DOI: 10.1002/jca.21618
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the CMNC and MNC apheresis protocol for the collection of T‐cells showed comparable outcome: An observational study in a single centre

Abstract: The CMNC and MNC protocols are reliable, efficient and comparable in performance parameters and cell composition of final product, respectively. One advantages of the CMNC protocol is the potential ability to tailor the cell composition of the final product accordingly to demands from cell processing laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The mean PLT attrition rate associated with apheresis using the Spectra Optia CMNC protocol was 48% (33.5%‐66.5%). Consistent with our results, previous human and canine apheresis studies described a decrease in PLT count (27.0%‐44.7%) after apheresis compared with the count before apheresis . Loss of PLTs is an adverse effect commonly associated with apheresis.…”
Section: Discussionsupporting
confidence: 91%
“…The mean PLT attrition rate associated with apheresis using the Spectra Optia CMNC protocol was 48% (33.5%‐66.5%). Consistent with our results, previous human and canine apheresis studies described a decrease in PLT count (27.0%‐44.7%) after apheresis compared with the count before apheresis . Loss of PLTs is an adverse effect commonly associated with apheresis.…”
Section: Discussionsupporting
confidence: 91%
“…The authors reported that the MNC program was associated with higher lymphocyte concentration in the final product [17], as found in our series. Putensen et al also compared CMNC and MNC for T cell collection in adults [18]; however, they observed similar efficiency (CE2%) between CMNC (54.7%) compared with MNC (50.4%).…”
Section: Discussionmentioning
confidence: 99%
“…With the unavailability of the Cobe Spectra, the Spectra Optia has been validated to a great extent in regard to primary, clinical properties of the apheresis products, and effects on clinical outcomes have been reported . Existing studies to address the potential impact of collection programs on later processing of these products focused on stem cells, used random donor cohorts, or analyzed the apheresis products without further functional testing . The impact of the apheresis method on downstream applications in research and clinical trials with cellular products that often include extensive handling (isolation, cryoconservation, enrichment, culture) has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%